Peran Ekosistem Laut dalam Konservasi Keanekaragaman Hayati Di Indonesia - Salayan, Lia Mandalika; Wulandari, Heni; Huda, Muhammad Komarul (Journal of Natural Sciences, 2024)
Indonesia's marine ecosystems play a crucial role in global biodiversity conservation, with regions rich in coral reefs, mangroves, and seagrass beds. The high marine biodiversity makes Indonesia home to various endemic species. However, these ecosystems face serious threats due to climate change, plastic pollution, overfishing, and coastal habitat degradation. This study aims to identify the role of marine ecosystems in biodiversity conservation in Indonesia, as well as the challenges they face. The research method used in this study includes literature review and analysis of marine conservation policies in Indonesia. The results show that Indonesia's marine ecosystems, including coral reefs, mangroves, and seagrass beds, significantly contribute to the sustainability of biodiversity and ecosystem balance. However, threats from both natural factors and human activities require more intensive conservation efforts. Conservation policies in several areas, such as Raja Ampat, have shown positive results, but there is a need for improvement in law enforcement and international collaboration. Therefore, effective and coordinated conservation efforts are essential to protect Indonesia's marine ecosystems and biodiversity for future generations